Anna Jelden: capstone - Jelden, Anna, artist (Colorado State University. Libraries, 2022)
The artist's statement: As a graphic designer and illustrator, my goal with every project I work on is to communicate effectively through the imagery and typography that I use. My work is colorful, fun, and whimsical with organic line work and textures that often take inspiration from nature. I believe that by observing the world with sensitivity, anything can become incredibly fascinating and inspiring, such as the veins on the underside of a leaf or the patterns and grooves on a rock created by erosion. I enjoy working digitally and with traditional media, often merging elements of both within my work.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design